A variety of gene polymorphisms associated with idiopathic granulomatous mastitis - DESTEK, SABAHATTİN; Destek, SABAHATTİN; Gul, Vahit Onur; Ahioglu, Serkan (My University, 2016)
Idiopathic granulomatous mastitis (IGM) is a rare and chronic inflammatory disorder. IGM mimics breast cancer regarding its clinical and radiological features. Etiology of IGM remains unclarified. Our patient was 37-year-old and 14 weeks pregnant. There was pain, redness and swelling in the right breast. The mass suggestive of malignancy was detected in sonography. Serum CA 125 and CA 15-3 levels were high. Genetic analysis was performed for the etiology. methylenetetrahydrofolate reductase (MTHFR) C 677 TT, beta-fibrinogen-455 G>A, plasminogen activator inhibitor (PAI)-1 5 G/5 G, angiotensin-converting enzyme (ACE) I/D mutation was found. IGM was diagnosed by cor biopsy. An association was also reported between breast cancer and mutations in MTHFR-C 677 T, PAI-1, ACE genes. Genetic polymorphisms may involve in the development of IGM as it was seen in our case. Further studies should be conducted to better clarify this plausible association.